PENGEMBANGAN PERANGKAT PEMBELAJARAN INSTALASI SISTEM OPERASI DENGAN MODEL PEMBELAJARAN BERBASIS PROYEK - Rajabi, Muhammad; Ekohariadi, Ekohariadi; Buditjahjanto, I.G.P. Asto (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
Abstract This research is a developmental research by developing the project based learning set of operating system installation. This research aims to find the feasibility of the learning sets which is developed and the study result after applying this learning set. The result which is expected in this research is the feasible project based learning set. The feasibility of this learning set meets the criteria of being valid, practical, and effective. Validity consists of content validity and constructs validity. Practical consists of easiness in applying the learning set. Effective is getting the students? response and achieving the learning goals. The model of developing this learning set is 4-D from Thiagarajan. Three are 1) define; 2) design; 3) develop, and 4) disseminate. The data is collected through observation, validation and test. Descriptive analysis is used to analyze the data. The result of the first research is the validity of the learning sets get the average score of 3.802. It meets the criteria of very valid. This scoring uses the instrument by using average of 3.3 and the criteria of valid. Second, the average of practical level is 3.80. It meets the criteria of very practical. The third result is the effectiveness of learning set which consists of students? response in the average percentage of 94% and the average of students? study result of 68.66. It meets the criteria of effective. The conclusion of this research is the learning set which is developed is feasible because it meets the criteria of valid, practical and efficient. Keywords: Developing Learning Set, Project Based Learning, Operating System Installation.